A legal study on cybercrime involving counterfeit pharmaceutical with references to the United States of America / Shafiqka Nisha Basah - Basah, Shafiqka Nisha (2017)
Counterfeit pharmaceutical cybercrime are a global problem and increasing in Malaysia, it has evolved in term of time and the advanced of technology. Counterfeit pharmaceutical is assumed as unregistered medicine in the current practice of investigation, no specific provision in curbing the problem to be charged in the court of law. This study is carried out to examine the existing provision in regulating counterfeit pharmaceutical cybercrime in Malaysia and whether the Sales of Drug Act 1952 are adequate enough to combat counterfeit pharmaceutical cybercrime. Other than that, identifying present laws and control of counterfeit pharmaceutical cybercrime in the United States of America to be adopted in Malaysia. Journals, articles and laws from Malaysia as well as the United States of America in regard to counterfeit pharmaceutical cybercrime has been reviewed and were used to support the information. The finding shows that the existing law is not comprehensive enough to protect Malaysian from the risk of counterfeiter. Inadequacy of law in Malaysia to combat issues in the cyber environment had left the enforcement agency warranting a control mechanism and enforcement power. Comparing with the legislation in the United States of America, the distribution of medicines is one of the safest systems in the world, and has a comprehensive law relating to pharmaceutical counterfeit cybercrime. Hence, authority is recommended to have specific Act that could protect consumer and improvise on the current provision.